What's in a name case? Some lessons for the debate over the free movement of same-sex couples within the EU - Van Den Brink, M (Cambridge University Press, 2016)
This Article engages the debate over the free movement of same-sex couples and explores what can, and should, be learned from the case law on the recognition of names. These “name cases” provide valuable lessons for both the proponents and opponents of same-sex marriage recognition. These cases show, first, that Member States are under the presumption to recognize marriages performed in other Member States. This Article also considers the importance of the national and constitutional identities of the Member States and suggests that there remains a possibility that Member States may justify the non-recognition of a marriage or deprive same-sex couples of some of the rights heterosexual married couples benefit from. The Article explores how the EU is confronted with a federal clash of values and offers some suggestions on how to solve this clash.